Fight corruption at the state and municipal levels in Russia: Following sociological (field) researches - Vorontsov, Sergey A.; Mamychev, Alexey Y.; Ponedelkov, Alexander V.; Kolesnik, Veronika V.; Boyko, Natalia A. (Linguistics and Culture Review, 2021)
The need to improve the efficiency of combating corruption presupposes an increase in the influence of ethical and moral norms on the observance of prohibitions, restrictions, and requirements established in order to counter corruption, as well as the development of additional mechanisms and tools for preventing corruption manifestations. Moreover, it is clearly not enough to legalize the norms of anti-corruption behaviour, through which law enforcement activities in this area could provide real results. Anti-corruption norms require not only legalization, but also legitimation, that is, recognition and support by citizens and society of this work as a whole. Only a combination of these two components can ensure an increase in the effectiveness of the prevention of corruption offenses in the Russian Federation. Legislative and law enforcement activities in the field of combating corruption systematically demonstrate not resistance, but a compromise, which negatively affects the authority of state bodies responsible for solving problems in the field of combating corruption, provokes legal nihilism among some citizens, disbelief in the goals and objectives declared by the anti-corruption policy.